Mesenchymal Stem Cell Secretome Effectiveness in Healing Chronic Tendon Injury: Procollagen Analysis and Histopathology in Rat Tendons - Sam ADP; Warsinggih W; Usman MA; Johan MP; Suroto H; Saleh MR; Sakti M; Zainuddin AA; Mubarak AF (Stem Cells and Cloning: Advances and Applications)
Andi Dhedie Prasatia Sam,1– 3 Warsinggih Warsinggih,4 Muhammad Andry Usman,5 Muhammad Phetrus Johan,5 Heri Suroto,6 M Ruksal Saleh,5 Muhammad Sakti,5 Andi Alfian Zainuddin,2,7 Andi Firman Mubarak1 1Faculty of Medicine, Universitas Muslim Indonesia, Makassar, Indonesia; 2Doctoral Study Program, Faculty of Medicine, Universitas Hasanuddin, Makassar, Indonesia; 3Stem Cell Research and Development Center, Universitas Airlangga, Surabaya, Indonesia; 4Department of Surgery, Faculty of Medicine, Universitas Hasanuddin, Makassar, Indonesia; 5Department of Orthopaedic and Traumatology, Faculty of Medicine, Universitas Hasanuddin, Makassar, Indonesia; 6Department of Orthopaedic and Traumatology, Faculty of Medicine, Dr. Soetomo General Academic Hospital, Universitas Airlangga, Surabaya, Indonesia; 7Faculty of Medicine, Universitas Hasanuddin, Makassar, IndonesiaCorrespondence: Andi Dhedie Prasatia Sam, Faculty of Medicine, Universitas Muslim Indonesia, Jl. Urip Sumoharjo No. km.5, Makassar, South Sulawesi, 90231, Indonesia, Tel +62411-443280, Fax +62411– 432730, Email andi.dhedie@umi.ac.idBackground: Chronic tendon injuries often lead to diminished healing capacity, necessitating innovative treatments. Mesenchymal stem cells (MSCs) secretome has emerged as a promising option for enhancing tendon repair through paracrine signaling. This study evaluates the effectiveness of MSC secretome, derived from tendon-derived stem cells (TDSCs) and adipose-derived stem cells (ASCs) in healing chronic Achilles tendon injuries in a rat model. The focus is on Procollagen Type I N-Terminal Peptide (PINP) and Procollagen Type III N-Terminal Peptide (PIIINP) levels, and histopathological changes.Methods: Fourteen adult male rats were divided into four groups: Group I (TDSC secretome), Group II (ASC secretome), Group III (combination of TDSC and ASC secretome), and Group IV (control). The healing response was assessed through PINP and PIIINP immunoserological markers, and histopathological changes were analyzed. The study adhered to ARRIVE and ICLAS guidelines and followed the National Institutes of Health (NIH) Guide for the Care and Use of Laboratory Animals.Results: The combination group showed significantly higher PINP levels compared to the control group (p = 0.004), suggesting enhanced Type I collagen synthesis. However, no significant differences in PIIINP levels were observed among the groups. Histopathological analysis showed no significant differences in collagen alignment or angiogenesis between treatment and control groups.Conclusion: The MSC secretome, particularly the combination of TDSCs and ASCs, may accelerate collagen Type I synthesis and improve tendon microstructure. This suggests their potential for treating chronic tendon injuries. However, further research with longer observation periods and clinical trials is crucial to confirm these findings and advance our understanding of tendon healing.Keywords: mesenchymal stem cell secretome, chronic tendon injury, tendon healing, procollagen markers, rat model